2005
DOI: 10.1007/11513988_46
|View full text |Cite
|
Sign up to set email alerts
|

A Policy Iteration Algorithm for Computing Fixed Points in Static Analysis of Programs

Abstract: Abstract. We present a new method for solving the fixed point equations that appear in the static analysis of programs by abstract interpretation. We introduce and analyze a policy iteration algorithm for monotone self-maps of complete lattices. We apply this algorithm to the particular case of lattices arising in the interval abstraction of values of variables. We demonstrate the improvements in terms of speed and precision over existing techniques based on Kleene iteration, including traditional widening/nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 19 publications
(38 reference statements)
0
72
0
Order By: Relevance
“…For that we use the following fixpoint transfer lemma: ∨ F V,I, • cl)). 6 Putting everything together, we obtain our main result for the time elapse operation: Abstract Semantics. So far, we have ignored the discrete transitions.…”
Section: Is a Point-wise Minimum Of Finitely Many Monotone Weak-affinmentioning
confidence: 94%
See 3 more Smart Citations
“…For that we use the following fixpoint transfer lemma: ∨ F V,I, • cl)). 6 Putting everything together, we obtain our main result for the time elapse operation: Abstract Semantics. So far, we have ignored the discrete transitions.…”
Section: Is a Point-wise Minimum Of Finitely Many Monotone Weak-affinmentioning
confidence: 94%
“…The approach of Gawlitza and Seidl [10] and the approach we present in this paper are both based on maxstrategy iteration. Costan et al [6] were the first who suggested to use strategy iteration for computing numerical invariants (for instance w.r.t. to template polyhedra).…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the lattice of intervals, the problem is studied in [57], [26] and [33]. [53] proposes a direct method to solve polyhedra fixpoint equations through the use of Farkas lemma and quantifier elimi-nation.…”
Section: Other Approaches To Compute Invariantsmentioning
confidence: 99%